The extreme rainfall gradient of the Cape Horn Biosphere Reserve and its impact on forest bird richness (Jan, 10.1007/s10531-022-02353-5, 2022) - Quilodran, Claudio S.; Sandvig, Erik M.; Aguirre, Francisco; de Aguilar, Juan Rivero; Barroso, Omar; Vasquez, Rodrigo A.; Rozzi Marin, Ricardo Roberto (My University, 2022)
In the original publication of the article, the affiliation of the sixth author, Rodrigo A. Vásquez was published incorrectly. The correct affiliation is provided in this Correction. The original article has been corrected. (3) Cape Horn International Center, Parque Etnobotánico Omora, Universidad de Magallanes, Puerto Williams, Chile. (4) Instituto de Ecología y Biodiversidad (IEB), Departamento de Ciencias Ecológicas, Facultad de Ciencias, Universidad de Chile, Santiago, Chile.
Keywords: Cape